2019
DOI: 10.1088/1742-6596/1363/1/012063
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of The E-Learning Concept In Education

Abstract: Application of web technology (Web-Based Education) can help learning process for an educational process can be called e-learning (electronic learning). The technology offered is speed and unlimited place and time to access information. Teaching and learning activities can be done easily by students anytime and anywhere. The boundaries of space, distance and time are no longer complex problems to be solved. The way to learn through the web is that there is access to information sources via the internet. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
0
5
0
8
Order By: Relevance
“…As online learning continues to be integrated into the foundations of higher education, the presence of a strong teacher and committed to student support must be a priority in the pedagogy of online teaching (Levy, 2017). Hence, Sudarsana et al (2019), suggested the development of e-learning makes three possibilities in the development of an internet based learning system, namely the web course, web centric course, and a web enhanced course.…”
mentioning
confidence: 99%
“…As online learning continues to be integrated into the foundations of higher education, the presence of a strong teacher and committed to student support must be a priority in the pedagogy of online teaching (Levy, 2017). Hence, Sudarsana et al (2019), suggested the development of e-learning makes three possibilities in the development of an internet based learning system, namely the web course, web centric course, and a web enhanced course.…”
mentioning
confidence: 99%
“…Diperlukan media berupa alat peraga dan KIT (Kotak Instrumen Terpadu) IPA serta tehnologi aplikasi digital yang dapat membantu guru untuk bisa melakukan pengajaran IPA dengan baik dan benar (Satria & Sari, 2018;Sudarsana, Mulyaningsih, et al, 2019;Sudarsana, Nakayanti, et al, 2019). Untuk saat ini pelatihan dan pemberian materi pelajaran sudah bisa dilakukan secara luring maupun daring (Sudarsana, Armaeni, et al, 2019). Penggunaan tehnology digital juga sudah banyak membantu para guru dalam melakukan pengajaran untuk siswanya bagi pembelajaran IPA atau materi selain IPA (Sudarmo, Rasmita, et al, 2021;Rahmat et al, 2021;Maruf et al, 2022).…”
Section: Pendahuluanunclassified
“…As blended and online learning continues to be included into the foundations of higher institutions, the availability of qualified educators who are dedicated to student support must be a priority in the pedagogy of online teaching and learning (Levy, 2017). The web course, web centered course, and web enhanced course are three alternatives in the construction of an internet-based learning system, as indicated by the growth of e-learning (Sudarsana et al, 2019). Learning, including online learning, has a number of benefits and drawbacks.…”
Section: Engagement Between Educators and Studentsmentioning
confidence: 99%